Women's right from the perspective of the purposes of Sharee'ah - El-Seoudi ,, Abdel Wadoud Moustafa Moursi; Mohd Nor, Amir Husin; Muhammad Husni, Ahmad; Omar, Ahmad Fakhri; Laluddin, Hayatullah; Ibrahim, Ibnor Azli; Samsudin, Muhamad Adib; Alias, Muhammad Nazir (Medwell Journal, 2012)
This research touches upon the rights of woman according to the perspective of Islamic Sharee‘ah (revealed laws). Researcher have divided these rights into three categories: Firstly, rights with which woman is distinguished away from man such as giving her a warm welcome at her birth and making Aqeeqah (slaughtering done for a new born) for her, giving her a beautiful name, taking care about her in her childhood, not preferring male child to her, honoring and protecting her when she becomes a wife, entitling her to have a specific obligatory share in inheritance. Secondly, rights in which woman is equal to man. They are the right of learning, her competence regarding bearing the responsibility of the religious obligations like man, respecting her will, the right of her independent financial liability and the right of work. Thirdly, the political rights of woman. They are her right in assuming the high posts (i.e., the political activities) such as the ministry, parliament, her right in assuming the great leadership of Muslims (president of the state), her right in assuming the judiciary posts. Also, researcher have explain these rights in detail according to the objectives of the Islamic Sharee‘ah and according to the requirements and necessities of the modern age and according to observing the matter of benefits and interests.